IMPLEMENTASI KEBIJAKAN PENYALURAN BANTUAN LANGSUNG TUNAI DANA DESA (BLT-DD) PADA MASA PANDEMI COVID-19 DI DESA SEA KABUPATEN MINAHASA - SASUWUK, CECELIA HELENIA; LENGKONG, FLORENCE; PALAR, NOVIE (Sam Ratulangi University, 2021)
Indonesia was hit by a major disaster, namely the Covid-19 pandemic, due to the Covid19 pandemic notonly having a social impact on Indonesia but also having a negative impact on the Indonesian economicsector, this has increased the number of poor people in Indonesia. launched a number of social assistance,one of which was direct cash assistance from village funds (BLT-DD) through this program the governmenthopes to help the poor in villages in meeting their daily needs during the Covid-19 pandemic, and one ofthem is the poor. Sea Village, Minahasa Regency which also received this program. So this study wasconducted to determine the implementation of the policy for distributing Village Fund Direct Assistance(BLT-DD) during the Covid-19 Pandemic in Sea Village, Minahasa Regency. This study uses descriptivequalitative method design, data obtained, data obtained from interviews, observations, and documentation.This study uses the theory of policy implementation from Van Meter and Van Horn which has 6 policyimplementation variables and from the results of this study that the BLT-DD program is still not runningwell because there is maladministration in its implementation.Keywords: Policy Implementation, Pandemic Covid-19, BLT-DD Program